Modelling, detecting and evaluating water ingress in aviation honeycomb panels; Quantitative InfraRed Thermography Journal; Vol. 14, iss. 2 - Vavilov V. P. Vladimir Platonovich; Pan Y.; Moskovchenko A. I.; Čapka A. (2017, 2017)
Title screen